1990
DOI: 10.1152/ajpgi.1990.259.2.g321
|View full text |Cite
|
Sign up to set email alerts
|

Gastric effects of TRH analogue and bicuculline injected into dorsal motor vagal nucleus in cats

Abstract: We investigated the gastric acid secretory and motility responses to microinjection into the dorsal motor nucleus of the vagus (DMV) of RX 77368, a stable thyrotropin-releasing hormone (TRH) analogue, and bicuculline, a gamma-aminobutyric acid (GABAA) receptor antagonist in ketamine-chloralose-anesthetized cats. Gastric acid output was collected every 15 min through a gastric cannula after saline flush and titrated to pH 7.0. Antral contractions were continuously recorded by an extraluminal strain gauge force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
21
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
5
21
0
Order By: Relevance
“…An early study found that micro‐injection of BMI into the DMV of cats, at a dose of ≈200 pmol, did not result in any gastric motility alterations 18 . However, subsequent reports have shown that BMI at this site dose‐dependently increases gastric acid secretion and antral contractility 9 , 10 and alters lower oesophageal sphincter pressure 10 . In the present study in rats, BMI (353 pmol) micro‐injected into the DMV, significantly increased IGP and pyloric motility, while the highest dose of BMI (1 nmol) significantly increased all indices of gastric motor function recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study found that micro‐injection of BMI into the DMV of cats, at a dose of ≈200 pmol, did not result in any gastric motility alterations 18 . However, subsequent reports have shown that BMI at this site dose‐dependently increases gastric acid secretion and antral contractility 9 , 10 and alters lower oesophageal sphincter pressure 10 . In the present study in rats, BMI (353 pmol) micro‐injected into the DMV, significantly increased IGP and pyloric motility, while the highest dose of BMI (1 nmol) significantly increased all indices of gastric motor function recorded.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, functional GI studies on GABAergic transmission in the DVC have only been performed in felines. In cats, micro‐injection of a GABA A antagonist, bicuculline methiodide (BMI) into the DMV produces dose‐dependent increases in gastric contractile activity and secretion 9 . 10 While electrophysiological studies in rats support the notion that neurones of the DMV receive a GABAergic inhibitory input, 8 , 11 it is not known whether GABA A receptors play a role in extrinsic control of gastric motor function in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory, GABAergic neurotransmission is arguably the most prominent regulator of ongoing vagal motorneuron activity (Travagli et al 2006). GABA A receptor antagonist application into the vagal complex significantly alters gastrointestinal and pancreatic function (Feng et al 1990;Mussa and Verberne 2008;Washabau et al 1995). Vagally mediated visceral functions related to energy homeostasis are thus tightly regulated by GABAergic signaling in the vagal complex.…”
mentioning
confidence: 99%
“…More specifically, a series of studies focused on the GI responses to microinjections of the GABA-and glutamaterelated substances in the brain stem. Microinjections of the specific GABA A antagonist bicuculline methiodide (BIC) into the DMV increase gastric acid secretion, intragastric pressure, and exocrine pancreatic secretions (27,44,53), suggesting that DMV neurons innervating the stomach and the exocrine pancreas receive tonic GABAergic inputs. Glutamate, in contrast, appears to exert site-specific effects on esophageal and gastric motility.…”
mentioning
confidence: 99%